(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The biocatalytic reduction of picolinaldehyde (Pyridine-2- carbaldehyde) In alcoholic mediumwas carried out using the microbial catalyst Baker’s yeast (Saccharomyces cerevisiae) free as well as inits immobilized form. The reduction product was isolated and purified by chromatographic techniquesincluding HPLC and characterized on the basis of spectral analysis.